Indigenous interfaces : spaces, technology, and social networks in Mexico and Central America - Gómez Menjívar, Jennifer Carolina; Chacón, Gloria Elizabeth (Critical issues in indigenous studies., 2019)
"This book explores how Indigenous people in Mesoamerica use social networks to alter, enhance, preserve, and contribute to self-representation"--Provided by publisher.